Te ara manukura : the factors motivating young Māori to enter university : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education at Te Kunenga ki Pūrehuroa, Massey University, Palmerston North, New Zealand - Cumming-Ruwhiu, Ani Sarah Marino (Massey University, 2012)
Higher education has a significant role to play in the development and progression of a people. Maori highlight for themselves that participation in tertiary education is important and necessary for advancements in matauranga Maori, economic development, environmental sustainability, health, social well-being and educational achievement. This thesis explores the factors that motivate young Maori to pursue a university degree. In addition, it explores the expectations of young Maori as a result of pursuing a university degree. Kaupapa Maori methodology underpins the theoretical framework used to direct all aspects of the research project. Te Manu Tukutuku offers a culturally appropriate theoretical framework that illustrates the fundamental principles that underpin the research. Participants were recruited through established social relationships and qualitative data was then gathered through semi-structured interviews with eleven young Maori university students in the North Island of New Zealand. A synthesis of the participants' responses and relevant literature reveal the key factors that motivate young Maori to pursue a university degree, that is, significant relationships and individual strengths. In addition, the expectations of young Maori as a result of pursuing a degree are shown in the context of building and maintaining relationships as well as individual excellence. The significant role of intrinsic and extrinsic motivators in the decision-making of young Maori is also discussed. The findings of this study are of importance to those involved with the effective achievement, motivation, educational transition and career development of young Maori. This thesis concludes with five key recommendations that relate to the findings of this study and suggestions for future research in this field.
Keywords: Maori (New Zealand people); Higher education; University education; Motivation